A Substrate-Independent Benthic Sampler (SIBS) for Hard and Mixed-Bottom Marine Habitats: A Proof-of-Concept Study - Keeley, Nigel; Laroche, Olivier; Birch, Murray; Pochon, Xavier (Frontiers in Marine Science, 2021)
Sea cage fish farms are increasingly situated over hard and mixed substrate habitats for production and waste-dispersion reasons; yet in many cases, these installations are not being effectively managed with respect to benthic impacts due to the lack of a practical sampling method. This study presents the first set of results from a newly developed Substrate Independent Benthic Sampler (SIBS) device that captures the unconsolidated organic and inorganic matter that overlies almost all substrates. The contents of the samples were analyzed using extracted environmental DNA (eDNA) followed by metabarcoding of the bacterial 16S rRNA gene. SIBS microbial assemblages reliably changed with proximity to farm and concurred with visual assessments of impact. Moreover, the approach appeared to be very sensitive with respect to the enrichment gradient, being able to discern influences at distances of 500–1500 m from the impact source. Other spatial differences, due to region and farm, were small in comparison, and the effect of the underlying substrate type was minor. The samples contained sufficient previously described bacterial bioindicator taxa from enriched sediments, such that a meaningful biotic index could be calculated, thereby placing them on a well-established benthic enrichment spectrum with established environmental thresholds. SIBS-derived bacterial data provide a powerful new approach for mapping spatial boundaries of farm effects irrespective of substrate type and topography. More importantly, the tool should also permit quantitative assessment of benthic enrichment levels irrespective of substrate type from depths of at least 100 m. It therefore has the potential to solve the hard-bottom problem that has until now prohibited effective environmental monitoring at mixed and hard-bottom locations.